Ornament size and colour as alternative strategies for effective communication in gliding lizards - Klomp, D.A.; Ord, T.J; Das, I.; Diesmos, A.; Ahmad, N.; Stuart-Fox, D. (Blackwell Publishing Ltd, 2016)
Sexual ornamentation needs to be conspicuous to be effective in attracting potential mates and defending territories and indeed, a multitude of ways exists to achieve this. Two principal mechanisms for increasing conspicuousness are to increase the ornament's colour or brightness contrast against the background and to increase the size of the ornament. We assessed the relationship between the colour and size of the dewlap, a large extendible throat-fan, across a range of species of gliding lizards (Agamidae; genus Draco) from Malaysia and the Philippines. We found a negative relationship across species between colour contrast against the background and dewlap size in males, but not in females, suggesting that males of different species use increasing colour contrast and dewlap size as alternative strategies for effective communication. Male dewlap size also increases with increasing sexual size dimorphism, and dewlap colour and brightness contrast increase with increasing sexual dichromatism in colour and brightness, respectively, suggesting that sexual selection may act on both dewlap size and colour. We further found evidence that relative predation intensity, as measured from predator attacks on models placed in the field, may play a role in the choice of strategy (high chromatic contrast or large dewlap area) a species employs. More broadly, these results highlight that each component in a signal (such as colour or size) may be influenced by different selection pressures and that by assessing components individually, we can gain a greater understanding of the evolution of signal diversity.